Strategic default and recognition of arbitral awards: comments on the Court Order 181/2021 of the Superior Court of Justice of Catalonia of 22 March 2021 - Ruiz Martín, Anna María (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The analysis hereby is based on the Court Order handled down by the Superior Court of Justice of Catalonia, in an arbitral award recognition proceeding of two foreign arbitral awards rendered by the International Commercial Arbitration Court of the Ukrainian Chamber of Commerce and Industry (the “ICAC”). The defendant replied to the recognition lawsuit considering that those arbitral awards were rendered by default due to the lack of notification of the arbitral proceeding. The Court Order has an interest for the Spanish case law on this topic, insofar it shows the tendency of the Spanish Superior Courts in recognizing the foreign arbitral awards, rather than its refusal, in cases such as the one at stake, when it is proven that the alleged default of the defendant might be regarded as a procedural strategy.